Oral administration of cernitin pollen extract (Cernilton®) for 30 days might be useful to avoid unnecessary biopsy in prostate biopsy candidates: A preliminary study. (25th March 2018) - Togo, Yoshikazu; Ichioka, Daishi; Miyazaki, Jun; Maeda, Yoshiko; Kameyama, Koji; Yasuda, Mitsuru; Hiyama, Yoshiki; Takahashi, Satoshi; Nagae, Hiroshi; Hirota, Seiichi; Yamamoto, Shingo
Abstract : Objectives: To assess the effect of cernitin pollen extract on serum prostate‐specific antigen level prostate biopsy candidates, and to develop an ideal protocol to avoid an unnecessary biopsy procedure. Methods: A total of 61 patients were administrated cernitin pollen extract tablets (two tablets t.i.d.) for 30 days, and then underwent a prostate biopsy with ≥12 systematic and targeted biopsy cores obtained. Serum prostate‐specific antigen levels were examined before and after administration of the pollen extract, and the change in serum prostate‐specific antigen and the rate of change were analyzed in relation to negative and positive biopsy results for cancer. Results: The mean change in serum prostate‐specific antigen and rate of change after administration of cernitin pollen extract in all patients were −0.6 ± 1.4 ng/mL and −7.6 ± 16.1%, respectively, which were significantly different from the baseline values ( P = 0.0003 and P = 0.0005, respectively). When prostate‐specific antigen change values and rates were compared between patients negative and positive for cancer, a significant difference between those groups was observed ( P = 0.04 and P = 0.03, respectively). Conclusions: The present study is the first to show that an ideal protocol using cernitin pollen extract has the potential to avoid an unnecessary prostate biopsy procedure in patients with elevated prostate‐specific antigen, possibly caused by inflammation. Additional studies with greater numbers of participants are required to confirm our findings and develop an ideal protocol.